The Roles and Safety of Journalists in Lithuanian Social Protests (2021–2023) - Majauskaitė, Raminta (Vilnius University Open Series, 2025)
As global dissatisfaction with the current situation grows, the number of social protests is increasing. These civic initiatives attract not only public attention but also the interest of the media, with journalists becoming one of the main sources of information. Although the primary goal of journalists is to provide accurate and impartial news, this is often hindered by protesters’ reluctance to engage with the media, their aggression, radical rhetoric, or other external factors. Recent protests in Lithuania, directed against pre-pandemic restrictions, were also marked by provocations, mockery, and violence. The object of this study is journalists who worked during the Great Family Defense March in May 2021, the protest near the Lithuanian Parliament in August 2021 that escalated into riots, the January 13th memorial in 2022, which turned into a protest against pandemic restrictions, and the 2023 farmers’ protests against the falling milk prices. The aim of this article is to identify the roles that the Lithuanian journalists assumed while covering these four protests and the challenges they were facing. Through qualitative content analysis, it was found that, due to external factors, journalists covering the protests often did not adhere to a single role. However, it became evident that the most common role they adopted was that of an observer oriented towards the public. The analysis also revealed that, due to role interactions, journalists could be assigned roles such as an observer oriented towards politics, a non-collaborative role, or an adaptive role. Furthermore, the research shows that, during social protests, Lithuanian journalists faced various threats that hindered the implementation of their professional principles.
Keywords: journalists’ roles; civil initiatives; journalists’ security; democracy